2015
DOI: 10.1093/pubmed/fdv121
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of patients and healthcare professionals of NHS cardiovascular health checks: a qualitative study

Abstract: BackgroundNHS Health Checks are a national cardiovascular risk assessment and management programme in England and Wales. We examined the experiences of patients attending and healthcare professionals (HCPs) conducting NHS Health Checks.MethodsInterviews were conducted with a purposive sample of 28 patients and 16 HCPs recruited from eight general practices across a range of socio-economic localities. Interviews were audio recorded, transcribed, anonymized and analysed thematically.ResultsPatients were motivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 25 publications
2
48
0
1
Order By: Relevance
“…Journal of Public Health. 2016;38:(3): 543–551 [ 36 ]. 28 patients and 16 HCPs Attend Deliver Patient behaviour change Interviews Riley, V.A., C. Gidlow, and N.J. Ellis, Uptake of NHS health check: issues in monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…Journal of Public Health. 2016;38:(3): 543–551 [ 36 ]. 28 patients and 16 HCPs Attend Deliver Patient behaviour change Interviews Riley, V.A., C. Gidlow, and N.J. Ellis, Uptake of NHS health check: issues in monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…It also forms part of the routine tools used in the NHS Health Check interview in England, which is primarily undertaken by other healthcare professionals, rather than by GPs themselves. 11 One in four people say they would be more active if advised by a GP or nurse. 12 Health professional-led PA interventions are very effective, with brief advice for PA having a number needed to treat of 12, up to 10…”
Section: Introductionmentioning
confidence: 99%
“…Welschen et al suggested that improvements in the perception of CVD risk did not influence patients’ attitudes and intentions to change their behaviour . The overall experience of attending the health check may have an impact on thinking about health and trigger behaviour change, regardless of CVD risk score . This might be explained by the population who take up the offer of a health check, where people who respond to the health check invitation might be more motivated to adopt a healthier lifestyle …”
Section: Discussionmentioning
confidence: 99%